Paralophiodon cf. leptorhynchum (tapiroidea, mammalia) à Vale Furado: contribution à la connaissance de l’éocène au Portugal - Antunes, M. Telles (2010)
A canine tooth from Vale Furado is classified as Paralophiodon cf. leptorhynchum. The genus Paralophiodon indicates an age from Lower Lutetian to Auversian, Middle Eocene. As it belongs in the lineage of P. leptorhynchum, possible age span is furth~L~uced from Middle Lutetian to Auversian. This conclusion remains valid or nearly so even in the less probable case of confusion with some form included in P. isselensis lineage. Our previous (1975) datation for sandstones and pelites from Vale Furado is thus confirmed, and more accurately recognized. Paralophiodon and the crocodilian Iberosuchus are a rather sound basis for correlation with stratigraphical units near Zamora and Salamanca in Spain.